2011
DOI: 10.1093/ecam/neq079
|View full text |Cite
|
Sign up to set email alerts
|

Dilong: Role in Peripheral Nerve Regeneration

Abstract: Dilong, also known as earthworm, has been widely used in traditional Chinese medicine (TCM) for thousands of years. Schwann cell migration and proliferation are critical for the regeneration of injured nerves and Schwann cells provide an essentially supportive role for neuron regeneration. However, the molecular mechanisms of migration and proliferation induced by dilongs in Schwann cells remain unclear. Here, we discuss the molecular mechanisms that includes (i) migration signaling, MAPKs (mitogen-activated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 100 publications
1
10
0
Order By: Relevance
“…Although, we could not demonstrate any toxic effects of EE in our experiments, to the best of our knowledge, it exhibited no gross toxic effects. Furthermore, our observation is in tune with the recent studies conducted by Chang et al [ 30 ] and Li et al [ 31 ], who have shown that EE can improve peripheral nerve regeneration and exhibits analgesic activity. Simultaneously, we used naloxone, an antagonist of opioid receptor [ 21 ] which plays a pivotal role in central nociceptive system, to block opioid receptor, and found that naloxone exhibited no effects on analgesic effects of EE in mice.…”
Section: Discussionsupporting
confidence: 92%
“…Although, we could not demonstrate any toxic effects of EE in our experiments, to the best of our knowledge, it exhibited no gross toxic effects. Furthermore, our observation is in tune with the recent studies conducted by Chang et al [ 30 ] and Li et al [ 31 ], who have shown that EE can improve peripheral nerve regeneration and exhibits analgesic activity. Simultaneously, we used naloxone, an antagonist of opioid receptor [ 21 ] which plays a pivotal role in central nociceptive system, to block opioid receptor, and found that naloxone exhibited no effects on analgesic effects of EE in mice.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies, however, have revealed that earthworm extract can be used in nerve regeneration treatments. Chang et al (2011a;2011b) reported that Dilong can promote Schwann cells proliferation and migration. Dilong is consisted of earthworm Pheretima aspergillum.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is of great significance to understand the mechanisms underlying SC migration after peripheral nerve injury and further identify targets to promote SC migration and peripheral nerve regeneration. Growth factors that regulate SC migration have been widely investigated, such as glial-cell-line-derived neurotrophic factor (GDNF) and neuregulin-1 (NRG1), which activate MAPK pathway to stimulate SC migration [22]. Our group has also identified several miRNAs that are involved in phenotype modulation of SCs during peripheral nerve regeneration [11][12][13].…”
Section: Discussionmentioning
confidence: 99%